A web-based and mobile patient-centered ''microblog'' messaging platform to improve care team communication in acute care. (18th August 2016) - Dalal, Anuj K; Schnipper, Jeffrey; Massaro, Anthony; Hanna, John; Mlaver, Eli; McNally, Kelly; Stade, Diana; Morrison, Constance; Bates, David W
Abstract : Communication in acute care settings is fragmented and occurs asynchronously via a variety of electronic modalities. Providers are often not on the same page with regard to the plan of care. We designed and developed a secure, patient-centered "microblog" messaging platform that identifies care team members by synchronizing with the electronic health record, and directs providers to a single forum where they can communicate about the plan of care. The system was used for 35% of patients admitted to a medical intensive care unit over a 6-month period. Major themes in messages included care coordination (49%), clinical summarization (29%), and care team collaboration (27%). Message transparency and persistence were seen as useful features by 83% and 62% of respondents, respectively. Availability of alternative messaging tools and variable use by non-unit providers were seen as main barriers to adoption by 83% and 62% of respondents, respectively. This approach has much potential to improve communication across settings once barriers are addressed.